Aquinas on Believing God - Siebert, Matthew Kent (2015)
Aquinas says that faith is belief about things one does not "see" for oneself. But if you do not see it for yourself, what makes your belief reasonable? Recent interpreters have missed a key part of Aquinas's answer, namely, that faith is believing God (credere Deo). In other words, they have not given sufficient attention to the formal object of faith. As a result, they overemphasize other parts of his answer Drawing partly on recent epistemology of testimony, I explain how the formal object of faith contributes to the justification of one's faith.
Keywords: BELIEF & doubt; FAITH & reason; Justification (Christian theology); theory of knowledge; Translators